Analysis of the Needs for the Development of Vocational Skills Education Program Evaluation Instruments - Dewi Kurniati; Munawir Yusuf; Subagya Subagya (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2023)
Educational programs in their implementation require evaluation so that the goals that have been set can be achieved. Program implementation must adapt to environmental conditions and existing developments in science and technology. The purpose of this study was to analyze the need for developing evaluation instruments for vocational skills education programs. The research method uses a descriptive qualitative research approach. The results of the study indicate that an evaluation instrument is needed that can evaluate the problems of a comprehensive vocational skills education program. The evaluation model that fits the needs is the CIPP model because it can evaluate comprehensively.